Isolation and Characterization of Thermotolerant Mungbean (Vigna Radiata L.) Rhizobial Isolate As Biofertilizer (Bangladesh Journal of Botany, 2023)
Rhizobia act as primary nitrogen fixing microorganisms in the root of leguminous plants. Efficient rhizobia are helpful in increasing productivity of legumes. In the present investigation a total of twenty rhizobial isolates were retrieved from root nodules of mungbean plants growing in field during summer season. On evaluation of plant growth promoting traits of all rhizobial isolates it was found that rhizobial isolate HSR1 had maximum indole acetic acid (IAA) production (58.83 μg/ml), ammonia excretion (4.78 μg/ml) and phosphate solubilization potential. Other plant growth promoting traits like aminocyclopropane- 1-carboxylic acid (ACC) deaminase activity, siderophore production and hydrogen cyanide (HCN) production were also exhibited by isolate HSR1. This isolate was able to survive 45ºC and exhibited plant growth promoting traits at high temperature. Genomic DNA extracted from isolate HSR1 was subjected to amplification of 16S rRNA gene for identification. The similarity searching of the sequence obtained after 16S rRNA gene sequencing showed 99% similarity with Sinorhizobium sp. T25, which was confirmed by morphological and biochemical tests. Presence of good plant growth promoting traits makes HSR1 a promising strain to be developed as biofertilizer to improve soil fertility and plant growth.Bangladesh J. Bot. 52(2): 217-224, 2023 (June)